Obtención, caracterización e incorporación del mucílago de malva (malva sylvestris) y su efecto en la clarificación del agua miel de agave (agave americana l.), para la producción de Miel. - Amaya Simba, Wilmer Wladimir (2022)
This study was carried out in Latacunga Canton, ‘Salache’ Neighborhood and in coordination with the Agave Project of ‘Universidad Técnica de Cotopaxi’ whose objective was to evaluate the clarifying effect of the mucilage on the plant called mallow (Malva sylvestris) in the agave mead (Agave americana L.), during the production process of agave honey. It began with the extraction of the mallow mucilage by using an experimental DBCA design with factorial arrangement (A x B), with four treatments and three repetitions. Therefore, two factors and two levels were taken into account: factor A; solution that is formed of vegetal material on volume of water (30g / 300ml - 30g / 450ml) and factor B; rotation time (3min - 5min). Through the characterization of the mucilage it was possible to determine the best treatment based on the viscosity, where an average higher than 25,2mPa.s in viscosity was obtained for the treatment t1. Once the best treatment was found, it proceeded to clarify the mead where a factorial design of (A x B) was used, with four treatments, two replicas, the A factor corresponds to the incorporation temperatures (60 ° C - 90 ° C) and factor B to the percentages of incorporation (20% - 30%). In the mead, initial physicochemical characteristics were determined, such as turbidity of 845 NTU, pH 5.38 and 10.4 °Brix. The clarification consists in incorporating the mucilaginous solution in the mead in order to eliminate the most solids in suspension. The best treatment is the t4 that is formed by the addition of the mucilage at 90 ° C temperature and 30% incorporation; where final averages of 269.5 NTU, 5.09 pH and 6.4 °Brix were obtained in clarified mead confirming that the mucilaginous solution has an effective clarifying effect. In addition, other parameters that were color, pH and °Brix were evaluated in the final product; being the best treatment the t4 with values of 222,01mm on the Pfund scale, 5,78 of pH and 68 ºBx. In the physicochemical analysis, the value for hydroxymethylfurfural is 16.4 mg / kg, confirming that, this value does not exceed the limit of 40 mg / kg established by the Ecuadorian Technical Standard INEN 1572 and the microbiological analysis is <10 CFU/g for both molds and yeasts. Mentioned parameters guarantee the quality and safety of the product, because they are complying with the limits established by certified standards.